2016
DOI: 10.1088/0964-1726/25/10/105005
|View full text |Cite
|
Sign up to set email alerts
|

Electrical percolation threshold of cementitious composites possessing self-sensing functionality incorporating different carbon-based materials

Abstract: An experimental study was carried out to understand the electrical percolation thresholds of different carbon-based nano-and micro-scale materials in cementitious composites. Multi-walled carbon nanotubes (CNTs), graphene nanoplatelets (GNPs) and carbon black (CB) were selected as the nano-scale materials, while 6 and 12 mm long carbon fibers (CF6 and CF12) were used as the micro-scale carbon-based materials. After determining the percolation thresholds of different electrical conductive materials, mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 33 publications
3
66
0
Order By: Relevance
“…Engineered cementitious composites (ECCs) are fiberreinforced cementitious composites with excellent tensile ductility and good durability under harsh environment [11][12][13][14][15][16][17][18][19]. e research found that incorporating conductive filler into ECCs could make it self-sensing [18][19][20][21][22][23]. Lin et al found that adding a small dosage of carbon black (CB) into the ECC system could enhance matrix tensile strength and achieve selfsensing ability [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered cementitious composites (ECCs) are fiberreinforced cementitious composites with excellent tensile ductility and good durability under harsh environment [11][12][13][14][15][16][17][18][19]. e research found that incorporating conductive filler into ECCs could make it self-sensing [18][19][20][21][22][23]. Lin et al found that adding a small dosage of carbon black (CB) into the ECC system could enhance matrix tensile strength and achieve selfsensing ability [20].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al found that adding a small dosage of carbon black (CB) into the ECC system could enhance matrix tensile strength and achieve selfsensing ability [20]. Al-Dahawi et al [21] found the percolation threshold of multiwalled carbon nanotubes, graphene nanoplatelets, carbon black, and carbon fiber in ECCs was around 0.55%, 2.00%, 2.00%, and 1.00%, respectively. ese carbonbased materials improved compressive strength and selfsensing ability under both compressive and flexural tests [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cement-based composites containing short carbon fibers have produced much higher gauge factors (up to 700) under compressive, tensile, and flexural loads [ 25 ]. Cement-based composites containing nanomaterials, e.g., carbon nanotubes and carbon nanofibers, have also demonstrated a high self-strain or -damage sensing capacity [ 4 , 14 , 15 , 19 , 20 , 21 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], even though achieving a uniform distribution of nanomaterials within cement-based composites remains quite challenging [ 33 ]. The distribution of nanomaterials could be enhanced by using surfactants, sonicators, and/or mechanical mixing procedures [ 10 , 12 , 15 , 22 , 27 , 30 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water to cementitious materials (PC + FA) ratio (W/CM) and fly ash to Portland cement ratio (FA/PC) were kept constants as 0.27 and 1.2, respectively during the preparation of mixtures. The dosage of CF as it was reported by Al-Dahawi et al [10]. This dosage was 1.00% by volume of mixture.…”
Section: Mixture Proportions and Mixing Methodsmentioning
confidence: 94%